Effect of adenosine triphosphate and some derivatives on cerebral blood flow and metabolism. - Forrester, T (1979)
1. Responses of cerebral blood vessels to peri- and intravascular doses of ATP (adenosine triphosphate) and some derivatives were studied in cat and baboon. 2. Perivascular application of ATP to cat pial arterioles gave a threshold dilatory effect at a concentration of 10(-11) M. This figure is comparable to the amount of ATP calculated to be released from electrically stimulated brain slices. 3. It is concluded that adenine nucleotides have a major role to play in the local control of cerebral blood flow. 4. Intracarotid injection of ATP showed a calculated threshold effect at 4 x 10(8) M in the cat and 4 x 10(-9) M in the baboon. 5. The threshold response of the vasculature to intracarotid adenosine lay between 4 x 10(-7) M and 4 x 10(-6) M in the baboon. Little effect was produced with AMP, pyrophosphate and inorganic phosphate. 6. Intracarotid ATP increased the oxygen consumption of the baboon brain parenchyma. This effect was attributed in part to an elevation of the cellular cyclic AMP levels. 7. Osmotic disruption of the blood-brain barrier in baboon did not affect the vasodilatory or metabolic effect of intracarotid ATP. 8. It is postulated that circulating purine compounds mediate a form of metabolic communication inthe body. Also, release of purine compounds from active local nerves might influence cerebral blood flow.